The effort to prevent stunting by training in making vegetable nuggets at Gombang, Boyolali - Fitria Dwi Rahmawati; Ahmad Riziq Maulana; Candra Tika Putri Maharani; Dwi Sukma Permadi Rini; Kelvin Matthew Richardo; Irvia Resti Puyanda (Universitas Muhammadiyah Malang, 2024)
The prevalence of stunting under five in Boyolali Regency was still unstable in 2018, at 10%; in 2019, it decreased to 7.2%, and until October 2020, it was 9.26% by looking at the height/age of each toddler. Nutrition is the main factor for forming the body's immune response, and malnutrition can cause a decrease in body immunity. The active participation approach in this community service is based on community independence. It aims to provide education about the importance of fulfilling nutrition needs through the consumption of nutritious food for Family Welfare Programme/Pemberdayaan Kesejahteraan Keluarga (PKK) Gombang Village mothers, especially in fulfilling daily family nutrition needs. The socialization is about making vegetable nuggets that can become local food creations while at the same time being able to fulfill daily food fiber needs. This activity is implemented through several stages: 1) Observation and request for willingness to cooperate with partners; 2) Formulation of Solution Steps; 3) Socialization; 4) Focus Group Discussion. The PKK's participation in this community service activity was very enthusiastic. This activity can provide knowledge about producing organic vegetable nugget processed products to form new entrepreneurs.